Analysis of Junior High School Students’ Science Process Skills in Environmental Pollution Based on Ethnoscience and Local Wisdom - Yasir, Mochammad; Khoiriyah, Khoiriyah (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Science process skills are skills in which studentâ€™s thinking skills are trained. The purpose of this study was to determine the level of science process skills at SMPN 2 Geger in terms of environmental pollution. The type of research used is descriptive quantitative non-expperimental. The research population was all students of class VII SMPN 2 Geger. Sampling using saturated sampling technique. The sample used in this study was 20 students of class VII SMPN 2 Geger. The instrument used was a test of studentâ€™s science process skills in the environmental pollution sub-material in the form of 12 essay questions. The research results obtained show that the average each student is included in the low category, with an average value of 32%.Â